Environmental Fluctuations and Stochastic Resonance in Protein Folding. Issue 9 (20th January 2016) - Dave, Kapil; Davtyan, Aram; Papoian, Garegin A.; Gruebele, Martin; Platkov, Max
Abstract: Stochastic resonance is a mechanism whereby a weak signal becomes detectable through the addition of noise. It is common in many macroscopic biological phenomena, but here we ask whether it can be observed in a microscopic biological phenomenon, protein folding. We investigate the folding kinetics of the protein VlsE, with a folding relaxation time of about 0.7 seconds at 38 °C in vitro. First we show that the VlsE unfolding/refolding reaction can be driven by a periodic thermal excitation above the reaction threshold. We detect the reaction by fluorescence from FRET labels on VlSE and show that accurate rate coefficients and activation barriers can be obtained from modulated kinetics. Then we weaken the periodic temperature modulation below the reaction threshold, and show that addition of artificial thermal noise speeds up the reaction from an undetectable to a detectable rate. We observe a maximum in the recovered signal as a function of thermal noise, a stochastic resonance. Simulation of a small model‐protein, analysis in an accompanying theory paper, and our experimental result here all show that correlated noise is a physically and chemically plausible mechanism by which cells could modulate biomolecular dynamics during threshold processes such as signaling. Abstract : The power of noise : The folding of protein VlsE can be enhanced by stochastic resonance when noise is added to a weak periodic thermal modulation that by itself is not sufficient to drive the folding reaction.